Shameless : Republicans' deliberate dysfunction and the battle to preserve democracy - Cohen, Brian Tyler (Harper, an imprint of HarperCollins Publishers, 2024)
From the first content creator to interview President Biden, leading progressive voice Brian Tyler Cohen takes a step back from the day-to-day news cycle to explain how American politics has turned into such a dumpster fire--and what Democrats need to do to get us out of it. In Shameless, Brian Tyler Cohen lays bare the long con of the modern Republican Party. While the radical right continues hiding behind gaslighting maneuvers, artificial slogans, and hollow catchphrases, Cohen's unflinching narrative illuminates the realities and dangers of the ever-widening gulf between the vaunted Republican brand and their actual behavior. With a foreword by Congressman Jamie Raskin, drawing on interviews and insights from Pete Buttigieg, Mehdi Hasan, Jen Psaki, and other luminaries of the Left, Cohen reveals: How Republicans have leaned on their historical branding to give themselves a permission structure to behave antithetically to everything they say; Why the mainstream media has proved itself a willing participant in this ongoing farce-- particularly since the rise of toxic, sensationalist MAGA mania; and What lessons Democrats can glean from a clear-eyed view of the landscape we're operating in--and the steps we must take to rebalance our political landscape. During this all-hands-on-deck moment in our history, Shameless is essential reading for those seeking to understand our dire situation, and a rallying cry for those fighting to preserve democracy.